Effects of IQW and IRW on Inflammation and Gut Microbiota in ETEC-Induced Diarrhea - Naiyuan Liu; Lingsi Zhou; Jun Fang; Hongmei Jiang; Gang Liu (Hindawi Limited, 2021)
Background/Aims. Changing gut microbiota is one of the most common causes of host gut inflammation. The active triple peptides, lle-Gln-Trp (IQW) and lle-Arg-Trp (IRW), cause remarkable changes to gut microbiota. The effects of the triple peptides IQW and IRW in gut-damage treatment were explored in this study via an enterotoxigenic Escherichia coli- (ETEC-) induced mouse model. Methods. The mice were randomly distributed into four groups: (a) control (CTRL) group, (b) ETEC group, (c) IQW-ETEC group, and (d) IRW-ETEC group. Villus length and crypt depth were measured after hematoxylin and eosin staining. The inflammatory reaction was analyzed via inflammatory cytokines (i.e., TNF-α, IL-1β, IL-6, and IL-10) using the enzyme-linked immunosorbent assay (ELISA). The microbiota in the colon was sequenced using 16S ribosomal RNA. Results. The villus length decreased, the crypt depth decreased, and the expression of inflammatory cytokines (i.e., TNF-α, IL-1β, IL-6, and IL-10) increased due to ETEC. In the IRW-ETEC and IQW-ETEC groups, the Shannon index decreased (P<0.05). IQW and IRW increased the abundance of Firmicutes, Proteobacteria, Clostridiales, Lachnospiraceae, and Alloprevotella; contrastingly, it decreased the abundance of Epsilonproteobacteria, Erysipelotrichales, Prevotellaceae, and Flavobacteriaceae compared to the ETEC group (P <0.05). Conclusion. This study ascertained that the addition of IQW and IRW could alleviate jejunal inflammation and increase microbiota community diversity.